Combined Bazedoxifene and Genistein Ameliorate Ovariectomy-Induced Hippocampal Neuro-Alterations via Activating CREB/BDNF/TrkB Signaling Pathway - Samak, Mai A.; Abdelrahman, Abeer A.; Samy, Walaa; Abdelrahman, Shaimaa A. (Current Molecular Pharmacology, 2023)
Objectives: The scientific research community devotes stupendous efforts to control the arguable counterbalance between the undesirable effects of hormone replacement therapy (HRT) and post-menopausal syndrome. The recent emergence of 3rd generation selective estrogen receptor modulators and phytoestrogens has provided a promising alternative to HRT. Hence, we assessed the potential effects of combined Bazedoxifene and Genistein on hippocampal neuro-alterations induced by experimental ovariectomy. Methods: For this purpose, we utilized forty-eight healthy sexually mature female Wistar rats assorted to control, ovariectomy (OVX), Genistein-treated ovariectomized (OVX+GEN) and Bazedoxifene and Genistein-treated ovariectomized (OVX+BZA+GEN) groups. Hippocampi samples from various groups were examined by H, silver stains and immunohistochemical examination for calbindin-D28k, GFAP, and BAX proteins. We also assessed hippocampal mRNA expression of ERK, CREB, BDNF and TrkB. Results: Our histopathological results confirmed that combined BZA+GEN induced restoration of hippocampal neuronal architecture, significant reduction of GFAP and BAX mean area % and significant upregulation of calbindin-D28k immunoexpression. Furthermore, we observed significant upregulation of ERK, CREB, BDNF and TrkB mRNA expression in the BZA+GEN group compared to the OVX group. Conclusion: Taken together, our findings have provided a comprehensive assessment of histological, immunohistochemical and cyto-molecular basis of combined Genistein and Bazedoxifene ameliorative impacts on hippocampal neuro-alterations of OVX rats via upregulation of Calbindin, CERB, BDNF, Trk-B and ERK neuronal expression.
Keywords: Bazedoxifene